One for all: a highly efficient and versatile method for fluorescent immunostaining in fish embryos - Inoue, Daigo; Wittbrodt, Joachim (PLOS ONE, 2011)
Background: For the detection and sub-cellular (co)-localization of proteins in the context of the tissue or organism immunostaining in whole mount preparations or on sections is still the best approach. So far, each antibody required its own fixation and antigen retrieval protocol so that optimizing immunostaining turned out to be tedious and time consuming. Methodology/Principal: Finding Here we present a novel method to efficiently retrieve the antigen in a widely applicable standard protocol, facilitating fluorescent immunostaining of both cryosections and whole mount preparations in zebrafish (Danio rerio) and medaka (Oryzias latipes). Conclusions/Significance: Our method overcomes the loss of sections and damage of tissue and cell morphology, and allows parallel immunostaining in multiple colors, co-immunostaining with fluorescent proteins in transgenic fish lines and in combination with whole mount in situ hybridization.